Using a stacker crane for sterile storage in the operating theatre: initial environmental microbiological qualification. (July 2022) - Faury, H.; Ducellier, D.; Cizeau, F.; Boquel, F.; Delaye, C.; Oudjhani, M.; Monpierre, L.; Lafont, C.; Decousser, J.-W.
Summary: Background: Adequate storage of sterile surgical devices must prevent contamination and the introduction of microbial contaminants inside the operating room. For functional and economic purposes, stacker cranes (STCs) could replace the traditional sterile storage room (TSSR). STCs are large, multi-stage, computer-assisted systems used to automatically store and retrieve loads from defined locations. However, their microbiological performance has not been evaluated. Aim: As part of the opening of a new building that included an operating theatre, we qualified a new STC and compared its microbiological control performance to that of the previous TSSR. Methods: From December 2020 to March 2021, 590 environmental specimens (air, N = 56; surfaces, N = 534) were collected and interpreted according to the NF S90-351 French Association for Standardization standards. Findings: Thorough surface disinfection was not sufficient for controlling microbial contamination in the STC. Thus, the initial qualification testing was conducted following an aggressive aerial chemical decontamination of the STC. Despite the lack of a HEPA filtered air system, the overall non-conformity rates were lower in the STC than in the TSSR (8.3% vs 21.4%, P =0.33 for air, respectively, and 9.7% vs 41.7% P <0.001 for surfaces). The air-controlled barrier in front of the loading zone appeared to be sufficient to prevent bacterial contamination. The presence of fungi must be carefully monitored. Conclusion: This is the first study supporting the contribution of STCs in saving space and improving the maintenance of sterile surgical device storage and availability under acceptable environmental conditions. Further studies are needed to assess the long-term microbiological contamination inside the STC.